2006
DOI: 10.1111/j.1440-1614.2006.01870.x
|View full text |Cite
|
Sign up to set email alerts
|

Season of birth, age and negative symptoms in a Xhosa schizophrenia sample from the Southern Hemisphere

Abstract: The results from our study support the existence of a seasonal birth pattern in an African schizophrenia population and suggest that avolition/apathy may underpin this seasonal pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In a further systematic review, we identified 10 disorders (intellectual disability, ASD, ADHD, schizophrenia, BID, MDD, AUD, Alzheimer's disease, anorexia nervosa, and bulimia nervosa) in 51 articles conducted in 25 countries involving 1 539 811 patients 1,3,5,6,27‐73 . The meta‐analytic results of our findings and included studies are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a further systematic review, we identified 10 disorders (intellectual disability, ASD, ADHD, schizophrenia, BID, MDD, AUD, Alzheimer's disease, anorexia nervosa, and bulimia nervosa) in 51 articles conducted in 25 countries involving 1 539 811 patients 1,3,5,6,27‐73 . The meta‐analytic results of our findings and included studies are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In a further systematic review, we identified 10 disorders (intellectual disability, ASD, ADHD, schizophrenia, BID, MDD, AUD, Alzheimer's disease, anorexia nervosa, and bulimia nervosa) in 51 articles conducted in 25 countries involving 1 539 811 patients. 1 , 3 , 5 , 6 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , …”
Section: Resultsmentioning
confidence: 99%